2015
DOI: 10.1080/13691058.2015.1084650
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on HIV testing among Latino youth

Abstract: Young Latinos aged 13-24 years in the USA are disproportionately impacted upon by HIV. Despite the elevated risk, lower rates of HIV testing have been documented among Latino youth relative to other racial/ethnic groups. The objective of the current study was to examine the influence of acculturation and cultural values on HIV testing among Latino youth. The study consisted of 51 sexually experienced young Latinos aged 13-16 years from a major city in the Southeastern USA. Participants completed a survey on HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Given the number of participants with family members in their social networks, HIV testing promotion efforts should also explore how to work with families to increase communication and challenge the multiple, intersecting forms of stigma that may shape use of HIV testing. The salience of family support has been more prominently explored in HIV literature with Latino youth (Ma & Malcolm, 2016; Muñoz-Laboy et al, 2009) and in Latin American settings (Barrington et al, 2016; Tucker et al, 2014), but our findings reaffirm the centrality of family ties for adult Latino immigrants in NC, especially those who migrate as adults.…”
Section: Discussionsupporting
confidence: 68%
“…Given the number of participants with family members in their social networks, HIV testing promotion efforts should also explore how to work with families to increase communication and challenge the multiple, intersecting forms of stigma that may shape use of HIV testing. The salience of family support has been more prominently explored in HIV literature with Latino youth (Ma & Malcolm, 2016; Muñoz-Laboy et al, 2009) and in Latin American settings (Barrington et al, 2016; Tucker et al, 2014), but our findings reaffirm the centrality of family ties for adult Latino immigrants in NC, especially those who migrate as adults.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, the Hispanic culture of familism embodies the belief in strong family ties that emphasize honor, respect, and support to members of the family, prioritizing family needs over the needs of the individual. Familism has been shown to deter HIV testing (Ma & Malcolm, ). Therefore, strategies to improve communication among partners and within families may increase testing rates among Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Living with a partner was not a critical factor to get an HIV test, which can be related to the concept of support networks prevalent in Hispanic culture. Familism values (Ma & Malcolm, ) also include extended family, which can provide support to maintain health even for women without a partner. Finally, the level of education in this sample was high (13 years on average, and less than 3% of the sample had 7 or fewer years of education), which could explain why this factor did not register as critical in the decision to obtain an HIV test.…”
Section: Discussionmentioning
confidence: 99%
“…Mexican and Mexican American groups), low educational level, male gender, and low self-perceived HIV risk. 30,31 Lopez-Quintero also found that married Latinos displayed lower intentions for HIV testing, which may relate to traditional conceptions of gender and sexual identity and assumptions around marital fidelity. 30…”
Section: Methodsmentioning
confidence: 96%